Character Education Children According to Abdullah Nashih Ulwan - Muhammad Hambal (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
The purpose of this study is to explore the urgency of Islamic education for children and how the theory of character formation of children according to Abdullah Nashih Ulwan. This research is a qualitative research with a type of library research, and the data analysis technique uses inductive and deductive. The findings of this study can be concluded: first, Islamic education is education oriented to the five pillars of religion, namely faith, etiquette, morals, worship, and muamalat. Two pillars are closely related to the affairs of the afterlife namely faith and worship. While the other three pillars are related to world affairs, namely morals, manners and muamalat. If the five pillars are considered in education, the education will give birth to human beings who have strong faith, true worship, good morals and manners, and are able to interact with the community and be involved in life in accordance with the skills (expertise) they have. Second, according to Ulwan, the theory of character formation of children starts from the time children are born, and the formation of children's character in order to become a human being (perfect human) is not enough just to reform the morals, but must pay attention to several aspects of coaching, both religious education, religious education, moral education, scientific education, and physical education. Because humans are not only like walking objects, but humans consist of spirits and bodies. The morals that are seen are the fruit of the faith and spirituality that exists in the soul and heart. Likewise man was created not to live alone, but he is a social creature that lives and mates with others. Keywords: Character Education, children, Ulwan